2012
DOI: 10.1002/sim.5428
|View full text |Cite
|
Sign up to set email alerts
|

Rare genetic variants and treatment response: sample size and analysis issues

Abstract: Incorporating information about common genetic variants may help improve the design and analysis of clinical trials. For example, if genes impact response to treatment, one can pregenotype potential participants to screen out genetically determined non-responders and substantially reduce the sample size and duration of a trial. Genetic associations with response to treatment are generally much larger than those observed for development of common diseases, as highlighted here by findings from genome-wide associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…To evaluate the validity of GVB, independent replication studies for an expanded gene–drug set with sufficient sample sizes in diverse ethnic groups are required as no novel variant was identified in the current study. A conventional single variant-based association test of rare variants requires infeasible magnitude of sample sizes (Bansal et al, 2010), but approaches that aggregate common, rare, and novel variants jointly will substantially reduce a required effective sample sizes (Witte, 2012). The robustness of the analysis framework shall further be improved as novel prognostic markers on 6-MP DIP are acquired.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the validity of GVB, independent replication studies for an expanded gene–drug set with sufficient sample sizes in diverse ethnic groups are required as no novel variant was identified in the current study. A conventional single variant-based association test of rare variants requires infeasible magnitude of sample sizes (Bansal et al, 2010), but approaches that aggregate common, rare, and novel variants jointly will substantially reduce a required effective sample sizes (Witte, 2012). The robustness of the analysis framework shall further be improved as novel prognostic markers on 6-MP DIP are acquired.…”
Section: Discussionmentioning
confidence: 99%
“…For serum urate-associated loci and gout, it has also been shown that rare variants contribute to disease pathogenesis 24 25. However, statistical confirmation of rare variants requires high-quality in-depth sequencing and large sample sizes, which is not the case for most GWAS performed to date in gout patients 26–28. With recent advancements in sequencing technologies, the study of rare-frequency and low-frequency variants has remarkably improved.…”
Section: Introductionmentioning
confidence: 99%
“…While recent technological advances have presented an opportunity for rare variant discovery, rare and low-frequency variant analysis requires special consideration. As these variants are individually uncommon, they are often statistically underpowered for detecting phenotypic association 9 . To circumvent this challenge, binning or collapsing methodologies are often utilized.…”
Section: Resultsmentioning
confidence: 99%